DESIGN APPLICATION OF INCOMING AND OUTGOING LETTER MANAGEMENT WEB-BASED AT CLINICS OF TREATMENT PALEMBANG IN MAGETAN EAST JAVA - Haviz Syah Viddyarta; Endra Rahmawati; Puspita Kartikasari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
From observations made at the Palembang Medicine Clinic, it was found that the management of incoming and outgoing letters still used the recording method in the notebook. Based on the results of discussions with the Palembang Medical Clinic, the management of incoming and outgoing letters like this raises a number of problems including frequent occurrence parties who need information about the letter, the officer is not easy to know the existence of the letter. The disposition process that still uses paper and every incoming letter and outgoing letter must be copied repeatedly for the filing process and the letter distribution process. Therefore, it is necessary to have an application for managing incoming and outgoing letters at the Palembang Medical Clinic which has a letter search feature, letter recording and letter disposition so that results can be obtained effectively and efficiently. The application will be designed with a web-based, because the web application data of incoming letter and outgoing letter can be more quickly connected from secretaries, managers, directors and employees found in Palembang Medical Clinic.Keywords: Application, Palembang Clinic, Incoming Letter, Outgoing Letter.